Cultural Representations of Borderline Personality Disorder - Munson, Katherine A.; Janney, Carol A.; Goodwin, Kelsie; Nagalla, Madhavi (Frontiers in Sociology, 2022)
Background/Objective Borderline Personality Disorder (BPD) is characterized by unstable interpersonal relationships, impulsivity, and self-harm. There are many distinct stressors that predispose individuals to develop BPD or engage in self-harm behaviors. The objective of this systematic review was to compare methods of self-harm and psychological stressors in BPD across different cultures. Methods A PubMed database search was conducted with the goal of capturing all articles (n = 22) that discussed methods of self-harm in BPD in any culture. Data extracted from the articles included methods of self-harm, psychological stressors, sample size, rurality, geographical location, and proportion of males to females. Results Key differences were noted in the methods of self-harm. Eastern nations (n = 5) reported higher rates of self-poisoning (60%) than Western nations (11%). Western nations (n = 9) reported higher rates of skin-mutilating behavior (100%) than Eastern nations (80%). Two of the articles included participants from rural settings, one in the Sundarban region of India and the other in Mississippi. Notably, the Sundarban region reported the highest rate of poisoning (93%) whereas the Mississippi region reported high rates of skin mutilation. Differences were also noted in psychological stressors as the rates of interpersonal problems were higher in Western than in Eastern nations. Conclusions Additional research should be conducted into the presentation of BPD in different cultures. An improved understanding of the cultural presentations of BPD could improve diagnosis and treatment in various populations.